Memaafkan Sebagai Faktor Penguat Kesehatan Mental Mahasiswa PAI Angkatan 22: Tinjauan Psikologis - Muhammad Khair; Surawan Surawan; Nabihah Husna Razali (Yayasan Cendekia Gagayunan Indonesia, 2025)
Mental health has become an increasingly relevant issue in modern society, particularly due to the influence of technology and social media, which tend to exacerbate individuals' psychological conditions. This study aims to examine the effect of forgiveness on the mental health of students in the Islamic Religious Education (PAI) Study Program, class of 2022. A quantitative approach with a correlational method was employed, involving 30 respondents selected through purposive sampling. The instrument used to measure forgiveness was the Heartland Forgiveness Scale, while mental health was assessed using the Warwick-Edinburgh Mental Well-being Scale. Pearson correlation test results indicated a very strong and significant relationship between forgiveness and mental health, with a correlation coefficient of 0.990 and a p-value of <0.001. These findings suggest that the higher the level of forgiveness, the better the students’ mental health condition. This research emphasizes the importance of forgiveness as a factor that strengthens psychological well-being and contributes to the development of more holistic psychological interventions. It is hoped that the results of this study can serve as a foundation for educational institutions to design programs that enhance students' mental health through the practice of forgiveness.